Positive psychology is value-laden—It's time to embrace it. Issue 3 (4th May 2021) - Prinzing, Michael M.
ABSTRACT: Evaluative claims and assumptions are ubiquitous in positive psychology. Some will deny this. But such disavowals are belied by the literature. Some will consider the presence of evaluative claims a problem and hope to root them out. But this is a mistake. If positive psychology is to live up to its raison d'être – to be the scientific study of the psychological components of human flourishing or well-being – it must make evaluative claims. Well-being consists in those things that are good for us, that make life go well. Thus, one cannot investigate this topic without making claims about what is good for people and what they have reason to do. It's time, therefore, to embrace the fact that positive psychology is value-laden. Doing so would benefit the field by allowing for more rigorous theorizing, and – perhaps counterintuitively – increasing the field's objectivity.